Determining the Toll and Capacity of a Highway to Be Constructed in Parallel with Subway. (27th May 2014) - Wu, Wen-Xiang; Shang, Hua-Yan
Abstract : This paper considers the problem of toll and capacity choice of a new highway with a bottleneck added onto an existing transit network under four ownership/tolling regimes: public fine toll, public flat toll, private fine toll, and private flat toll. Whenever fine toll and flat toll are imposed, in a competitive highway/transit network with constant returns to scale in road construction, an optimally designed and priced privately owned highway would produce positive net benefit justly equal to the total markup with respect to all autocommuters, whereas an optimally designed and priced publicly owned highway would lead to a deficit; that is, the toll revenues are insufficient to cover its all costs. The economic conditions to invest a new road are investigated under different ownership/tolling regimes.